2013
DOI: 10.3389/fnhum.2013.00479
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Real-Time Resting-State fMRI Using Multi-Slab Echo-Volumar Imaging

Abstract: We recently demonstrated that ultra-high-speed real-time fMRI using multi-slab echo-volumar imaging (MEVI) significantly increases sensitivity for mapping task-related activation and resting-state networks (RSNs) compared to echo-planar imaging (Posse et al., 2012). In the present study we characterize the sensitivity of MEVI for mapping RSN connectivity dynamics, comparing independent component analysis (ICA) and a novel seed-based connectivity analysis (SBCA) that combines sliding-window correlation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 93 publications
(151 reference statements)
7
76
1
Order By: Relevance
“…The negative change is strong in CSF and thus cannot be solely a classical BOLD susceptibility change. Moreover, in-flow effects would rather result in positive in signal changes 33 and would in any case not be expected given the 3D MREG excitation. The negative signal changes are more likely due to a disruption of steady-state precession caused by CSF impulses, which lead to incomplete T2 relaxation.…”
Section: Cardiovascular Brain Impulse Propels Csf Centrifugallymentioning
confidence: 99%
“…The negative change is strong in CSF and thus cannot be solely a classical BOLD susceptibility change. Moreover, in-flow effects would rather result in positive in signal changes 33 and would in any case not be expected given the 3D MREG excitation. The negative signal changes are more likely due to a disruption of steady-state precession caused by CSF impulses, which lead to incomplete T2 relaxation.…”
Section: Cardiovascular Brain Impulse Propels Csf Centrifugallymentioning
confidence: 99%
“…Multiple high temporal resolution fMRI sequences were developed (Posse et al, 2012;Asslander et al, 2013;Chang et al, 2013) to help shed some light on basic neuroscience questions as well as increased clinical impact in understanding some neurodegenerative disorders that rely on functional imaging (Posse et al, 2013). Functional connectivity and epilepsy studies using those high resolution sequences have been reported (Posse et al, 2012;Lee et al, 2013;Jacobs et al, 2014), but the need for a sub-second scale fMRI sequence is still uncertain given the sluggish and slow BOLD response.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent sequence, echo-shifted InI, was able to perform fMRI at a TR of 30 ms and to show group-level hemodynamic responses timing differences as low as 50 ms in the visual system (Chang et al, 2013), suggesting that subtle neural activation timing are tractable with fMRI. Fast Multi-slab echo-volumar imaging (EVI) was shown to reveal resting state networks with high sensitivity in measurement times as short as 75 s (Posse et al, 2012;Posse et al, 2013), having clinical implications for patient populations with variable degrees of cooperation. Other connectivity studies relying on such fast sampling sequences have indeed shown increased statistical power and revealed interesting brain networks oscillating in the 0.5-0.8 Hz band, well beyond the very low frequency range (0.01-0.1 Hz) traditionally studied using the conventional EPI sequence .…”
mentioning
confidence: 99%
“…The capacity of ICA to find common patterns of activation in huge cohorts of subjects is demonstrated by the parallel computing approach described by Kalcher et al (2012) and the use of ICA with cutting edge MR methods are presented by the groups of Stefan Posse [Echo Volume Imaging (Posse et al, 2013)], Markus Barth [EEG-fMRI (Meyer et al, 2013) and Ultra-Fast Generalized Inverse Imaging (Boyacioglu et al, 2013)], and Jorge Jovicich [realtime fMRI (Soldati et al, 2013a,b)]. …”
mentioning
confidence: 99%